Strategic Drivers of Mangrove Ecotourism Development: Evidence from Mimika Regency, Indonesia - Maria Mote; Trasna Putra Urip S; J. Ary Mollet (Global Academy of Multidisciplinary Studies, 2026)
Purpose: This study aimed to identify government strategies for developing mangrove ecotourism in Pomako, Mimika Regency, Papua Province, Indonesia, and determine priority strategies for sustainable ecotourism development based on strategic factor analysis. Research Methodology: A qualitative descriptive design was used, with data collected through questionnaires, interviews, observations, and documentation, and then analyzed using SWOT through IFAS and EFAS matrices involving purposively selected tourism staff and local community respondents. Results: The IFAS strength score was 4.489, and the weakness score was -1.785, yielding a net internal score of 2.703. The EFAS opportunity score was 4.606, and the threat score was -1.982, yielding a net external score of 2.624. The Cartesian coordinates (2.703; 2.624) position the site firmly in Quadrant I, corresponding to the SO (Strength-Opportunity) strategy, an aggressive growth orientation. Conclusions: Pomako's mangrove ecotourism possesses the internal assets and external conditions necessary to pursue an aggressive growth strategy. An integrated approach combining infrastructure investment, evidence-based marketing, and institutional strengthening is essential to sustain growth, protect ecosystems and maximize community welfare benefits. Limitations: This study has several limitations, including its focus on a single ecotourism site, which limits the generalizability of the findings to other contexts and locations. Additionally, the small purposive sample and cross-sectional nature of the study restrict the ability to draw statistical inferences and account for changes in the strategic landscape over time. Contributions: This study offers valuable insights into the strategic development of mangrove ecotourism in Pomako, Mimika Regency, Papua, by identifying key factors influencing growth through SWOT analysis.